2019
DOI: 10.1038/s41598-019-53982-w
|View full text |Cite
|
Sign up to set email alerts
|

Cromolyn sodium delays disease onset and is neuroprotective in the SOD1G93A Mouse Model of amyotrophic lateral sclerosis

Abstract: Accumulating evidence suggests that neuroinflammatory processes are implicated in the initiation and progression of amyotrophic lateral sclerosis (ALS). Previous reports have demonstrated an increase in microgliosis and astrogliosis in the lumbar spinal cord of SOD1G93A transgenic mice before the onset of symptoms, a neuroinflammatory response which correlated with disease progression. Importantly, early stage homeostatic microglia enhanced motor neuron survival, while pro-inflammatory microglia were toxic to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…Neither cromolyn or F-cromolyn had any signi cant effect on altering IL-10 expression in HMC3 microglia. Additionally, in vivo experiments with the SOD1 G93A mice model of ALS found that 5 days per week intraperitoneal cromolyn treatment for approximately two months beginning 60 days postnatal until onset of major paralysis did not signi cantly alter IL-10 levels in spinal cord lysates despite mice exhibiting delayed onset of disease [23].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Neither cromolyn or F-cromolyn had any signi cant effect on altering IL-10 expression in HMC3 microglia. Additionally, in vivo experiments with the SOD1 G93A mice model of ALS found that 5 days per week intraperitoneal cromolyn treatment for approximately two months beginning 60 days postnatal until onset of major paralysis did not signi cantly alter IL-10 levels in spinal cord lysates despite mice exhibiting delayed onset of disease [23].…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, cromolyn reduced the levels of pro-in ammatory cytokines and mast cell activity in SOD1 transgenic mouse models from ALS [23].…”
Section: Introductionmentioning
confidence: 94%
“…Second, similar to rofecoxib in the current study, the anti-inflammatory drugs, such as D-penicillamine, a copper chelator, and sulindac, a COX-2 inhibitor, can only extend the survival time by about 10% (Hottinger et al, 1997;Kiaei et al, 2005). Like rofecoxib, several other anti-neuroinflammatory interventions have also yielded better effects in delaying disease onset than in prolonging survival in SOD1 G93A mice, such as cromolyn sodium (Granucci et al, 2019), tempol (Chiarotto et al, 2019), and lysine acetylsalicylate (Barneoud and Curet, 1999). Third, many other mechanisms besides neuroinflammation have been confirmed to be related to the pathogenesis of ALS, such as protein aggregation (Brown and Al-Chalabi, 2017), oxidative stress (Bozzo et al, 2017), glutamate excitotoxicity (Blasco et al, 2014), autophagy abnormality (Nassif and Hetz, 2011), mitochondrial structure and function abnormality (Golpich et al, 2016), and endoplasmic reticulum stress (Matus et al, 2013).…”
Section: Discussionmentioning
confidence: 65%
“…Previous studies have shown that administration of mast cell inhibitor drug cromolyn suppresses neuroinflammation, brain damage, BBB stability, and improves cognitive disorder after neurotrauma in animals (Jin et al 2007;Mattila et al 2011;McKittrick et al 2015;Valle-Dorado et al 2015;Zhang et al 2016). Previous studies suggested that cromolyn treatment provided neuroprotective effects by promoting microglial phagocytosis, reducing proinflammatory microglial state, and increasing the anti-inflammatory microglial state, and inhibiting the severity of disease (Granucci et al 2019;Zhang et al 2018). One recent study indicates that cromolyn decreases sensorimotor dysfunction and hippocampal damage in severe TBI in rats (Segovia-Oropeza et al 2020).…”
Section: Discussionmentioning
confidence: 99%